Chirality in 2D Cosserat media related to stretch-micro-rotation coupling with links to granular micromechanics. (1st October 2020) - Giorgio, Ivan; dell'Isola, Francesco; Misra, Anil
Abstract: Cosserat continuum model has attracted increasing interest for describing the mechanical behavior of microstructured solids. Existing formulation of Cosserat continuum model often overlooks chiral effects that arise from coupling between stretching deformations and the micro-rotation. Here, we introduce an extended Cosserat model that accounts for such a coupling. We discover the links of the extended model to the mechanics of granular materials and identify the continuum and grain-scale parameters that are the source of postulated chirality. The micro-rotation is shown to be related to the coupling of shear and normal responses of grain-pair interactions. The consequences of this chirality are then explicated with the aid of numerical examples. Through parametric studies we also demonstrate the possibility of measuring the effects of this type of chirality in experiments.